The Impact of Cultivation of Medicinal Plants on the Economic Income of Rural Settlements Case study of Kalat city villages - Alipour Khesht, Mansoureh (2021)
Medicinal plants, as part of natural resources, have been one of the most important sources of human food and medicine for generations. Diversification of the rural economy is considered as a tool to accelerate economic development at various levels¸ this approach is considered as one of the most important strategies for the development and economic sustainability of rural settlements in Iran¸ because it has a great effect on promoting the welfare and security of the region's economy. According to the economic policies of the country based on the development of non-oil exports, it is necessary to pay attention to the export of agricultural products¸ therefore, by planting valuable medicinal species, it is possible to plan the texts, while developing the economy and provision the needs of domestic industries, and it also earned significant foreign exchange earnings from the export of medicinal plant products. The aim of this study was to investigate the effect of cultivation of medicinal plants on the economic development of rural settlements (case study of villages in Kalat city). The present research is applied in terms of purpose and is descriptive-analytical in terms of method. The sample population includes 7 villages of Kalat city (Abgarm, Aghdash, Qara Tikan, Garou, Qoleh Zoo, Sini and Soroud) with 1589 families, which amount to 5283 people. According to the research results, planting medicinal plants, on average, generates 523.6 more in revenue generation than planting crops.